Surprised by Sin: Medical Metaphors and Secular Eschatology in Ian McEwan's Saturday. Issue 1 (16th June 2022) - Malla, Samik
Abstract: Critics have tended to read Saturday through the lens of rationalism, or its failings thereof. This article suggests, perhaps counter-intuitively, that it may be read as an allegory of theological yearning in a world bereft of magic. It is not to cast aspersions on McEwan's commitment to reason, but to make a case that deep-rooted religious impulses adapt to the dictums of secular materiality and that, instead of abandoning metaphysics, Saturday secularizes it.